Factors Predicting Paternal Depression in Postnatal Period - ทูลธรรม กัญยา; ศรีอาภรณ์ พรรณพิไล; เจริญสันติ จันทรรัตน์ (Nursing Journal CMU, 2017)
Paternal depression during the postnatal period is an important emotional change that has a negative effect on the physiology, psychology, role of fathers, families and society. The purpose of this predictive correlational research study was to determine correlations between and the predictability of age, educational level, paternal status, self-esteem, marital relationship and paternal depression during the postnatal period. Data were collected through three self-reports, involing 84 fathers of children aged 6 and 8 weeks old at Health Promotion Hospital Health Promotion Center Region 1 Chiang Mai and Maharaj Nakorn Chiang Mai Hospital during March to June, 2015. The research instruments used were the Edinburgh Postnatal Depression Scale (EPDS), the Rosenberg*Self-esteem*Scale (RSE) and the Marital Relationship Questionnaire. Data were analyzed using descriptive statistics, Eta correlation, Pearson product-moment correlation coefficient and multiple regression analysis. Results of the study revealed that: Paternal depression during the postnatal period was documented at 21.40% with a mean score of 5.92 (S.D. = 3.76). There was a statistically significant low positive correlation between paternal status and paternal depression (Eta. = .22, p = .05), a moderate negative correlation between self-esteem and paternal depression (r = -.47, p < .01), and a high negative correlation between marital relationship and paternal depression during the postnatal period (r = -.50, p < .01) Age, educational level, paternal status, self-esteem, and marital relationship accounted for 32.80 % of the variability in paternal depression (p < .05). The results of this study can be used as guidelines for further study about predicting factors of postnatal depression among Thai fathers and used as data to plan nursing interventions to reduce risk factors of paternal depression during the postnatal period.